Salting-in with a salting-out agent: explaining the cation specific effects on the aqueous solubility of amino acids - Tomé, L.I.N. (2014)
Although the understanding of ion specific effects on the aqueous solubilities of biomolecules is crucial for the development of many areas of biochemistry and life sciences, a consensual and well-supported molecular picture of the phenomena has not yet been established. Mostly, the influence of cations and the nature of the molecular interactions responsible for the reversal of the Hofmeister trend in aqueous solutions of amino acids and proteins are still defectively understood. Aiming at contributing to the understanding of the molecular-level mechanisms governing the cation specific effects on the aqueous solubilities of biocompounds, experimental solubility measurements and classical molecular dynamics simulations were performed for aqueous solutions of three amino acids (alanine, valine, and isoleucine), in the presence of a series of inorganic salts. The evidence gathered suggests that the mechanism by which salting-in inducing cations operate in aqueous solutions of amino acids is different from that of anions, and allows for a novel and consistent molecular description of the effect of the cation on the solubility based on specific interactions of the cations with the negatively charged moieties of the biomolecules.